2021
DOI: 10.1371/journal.pone.0256258
|View full text |Cite|
|
Sign up to set email alerts
|

The Cardiorespiratory fitness of children and adolescents in Tibet at altitudes over 3,500 meters

Abstract: Background Cardiorespiratory fitness (CRF) is the core element of health-related physical fitness evaluation. High pressure and low oxygen in Tibet (over 3,500 m above sea level) may negatively impact the residents’ CRF. The 20-m shuttle run test (20mSRT) is the most popular field-based assessment and estimate of CRF in children and adolescents worldwide. However, normative CRF data for the children and adolescents residing in China’s plateau region are unavailable, which prevents comparability among those liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
0
9
1
Order By: Relevance
“…This could be due to sex differences in body fat tissue and lean body weight composition, as well as differences in hemoglobin content between pubertal males and females, which is a critical component of the sex-based variations in CRF. 38 Furthermore, the results of this study revealed a significant difference between sexes on the flamingo test (P = .01), with males scoring higher. A similar study addressed the associations between gross motor coordination and academic achievement in elementary school children in Portugal 6 found that males had significantly higher average levels of gross motor control and fitness than females, which could be attributed to males engaging in more physical activity and sports than females.…”
Section: Discussionmentioning
confidence: 57%
“…This could be due to sex differences in body fat tissue and lean body weight composition, as well as differences in hemoglobin content between pubertal males and females, which is a critical component of the sex-based variations in CRF. 38 Furthermore, the results of this study revealed a significant difference between sexes on the flamingo test (P = .01), with males scoring higher. A similar study addressed the associations between gross motor coordination and academic achievement in elementary school children in Portugal 6 found that males had significantly higher average levels of gross motor control and fitness than females, which could be attributed to males engaging in more physical activity and sports than females.…”
Section: Discussionmentioning
confidence: 57%
“…There have also been studies in other countries on indigenous people's physical tness and sports performance, for example, a recent study conducted by Chiluwal shows that indigenous students in Nepal's Lamjung district are physically better than non-indigenous students [8]. In addition, Fan et al argued that Tibetan children and adolescents generally have better cardiopulmonary tness and basic exercise abilities than Han counterparts because they have grown up in a high-altitude environment [9]. However, cardiorespiratory tness, as an indicator of healthy physical performance, is directly related to factors such as exercise performance and cardiovascular disease risk [10].…”
Section: Introductionmentioning
confidence: 99%
“…To adapt to chronic hypoxia, Chinese Tibetans exhibit important physiological and morphologic characteristics of the cardiopulmonary, system such as large chest dimensions [23,24]. A recent report suggested that children and adolescents aged 7-18 years residing above 3500 m in Tibet displayed lower CRF compared with their counterparts from the plains area [25]. Therefore, it is unreasonable to adopt the Chinses national standard to evaluate the CRF of Tibetan children and adolescents at high altitudes, and it is necessary to establish reference values of CRF for this population.…”
Section: Introductionmentioning
confidence: 99%